Authoritarian legality in Asia : formation, development, and transition / edited by Weitseng Chen, Hualing Fu. - Chen, Weizeng, 1972--; Fu, Hualing (Cambridge University Press, 2019)
A cluster of Asian states are well-known for their authoritarian legality while having been able to achieve remarkable economic growth. Why would an authoritarian regime seek or tolerate a significant degree of legality and how has such type of legality been made possible in Asia? Would a transition towards a liberal, democratic system eventually take place and, if so, what kind of post-transition struggles are likely to be experienced? This book compares the past and current experiences of China, Hong Kong, South Korea, Japan, Taiwan, Singapore, and Vietnam and offers a comparative framework for readers to conduct a theoretical dialogue with the orthodox conception of liberal democracy and the rule of law.